EVALUATION OF HANDLING OF B3 LOADING (DANGEROUS AND TOXIC GOODS) ON SHIPS AT SEI SELARI FERRY PORT - Surnata, Surnata; Triwahyuni, Siti Nurlaili; Agustini, Elfita; Qussay, Agni (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2024)
in accordance with KP-DRJD 539 of 2022 concerning Guidelines for Planning, Development and Performance Evaluation of River, Lake and Ferry Ports, it is worthy of evaluation in order to determine the extent of operational performance that has been implemented so far. The purpose of this study is to determine the performance weight of the Kuala Tungkal Ferry Port. In this study, the researcher used a quantitative research method, namely collecting and processing figures that have been obtained through surveys. Based on the results of the study, it is known that the Kuala Tungkal Ferry Port has worked with an assessment weight of 76.7 and the category